2008
DOI: 10.1192/bjp.bp.107.045450
|View full text |Cite
|
Sign up to set email alerts
|

Neurological abnormalities and cognitive ability in first-episode psychosis

Abstract: Higher rates of primary and motor coordination signs are not associated with lower cognitive ability, and are specific to the presence of psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 27 publications
2
32
1
Order By: Relevance
“…As expected, the current IQ of patients was lower than their premorbid IQ on average (see also Dazzan et al, 2008). We calculated a difference score (IQ minus premorbid IQ) in order to see whether the estimated deterioration was associated with cannabis use (see also Leeson et al, 2011), and found this to be the case.…”
Section: Difference Between Iq and Premorbid Iq In Relation To Cannabmentioning
confidence: 80%
“…As expected, the current IQ of patients was lower than their premorbid IQ on average (see also Dazzan et al, 2008). We calculated a difference score (IQ minus premorbid IQ) in order to see whether the estimated deterioration was associated with cannabis use (see also Leeson et al, 2011), and found this to be the case.…”
Section: Difference Between Iq and Premorbid Iq In Relation To Cannabmentioning
confidence: 80%
“…Being one of the common neuropsychological tests to assess the executive function of mental set shifting, the TMT B is required to search for and connect targets containing digits and letters with a pencil in ascending order, alternating between digits and letters. In order to exclude that the observed results are due to neurological soft signs that have been reported in schizophrenia (Chan and Gottesman 2008;Dazzan et al 2008;Gupta et al 1995), we compared the results to the association between Crus I/II and TMT A. TMT A involves the connection of targets but consisting of digits only, so that the task switching component is absent but the motoric component is present as well. Interestingly, we only found a significant association between GM in Crus I/II and the Brain Struct Funct (2012) 217:523-529 527 TMT B, not TMT A.…”
Section: Discussionmentioning
confidence: 92%
“…in subjects who do not respond to treatment. Relevant to this notion is the observation that neurological soft signs, often considered to be an index of neurodevelopmental disturbances in schizophrenia, 67 are related to both reduced gyrification 68 and poor response to antipsychotics in psychosis. 69 Moreover, unlike responders, the nonresponders showed no diagnostic differences in gyrification.…”
mentioning
confidence: 97%